Fabrication and characterization of porous cordierite ceramics prepared from fly ash and natural minerals. Issue 15 (15th October 2019) - Wang, Shaoxin; Wang, Hao; Chen, Ziwei; Ji, Ru; Liu, Lili; Wang, Xidong
Abstract: Low cost, single-phase porous cordierite ceramics are successfully synthesized by in-situ solid-state reactions from fly ash, quartz, and magnesite. The effects of sintering temperature and magnesite content on phase transformation, open porosity, bulk density, mechanical properties, and microstructure are carefully investigated. Factsage analyses are carried out to calculate the isopleth diagrams, and the results agree well with the experimental outcomes. Thermal gravimetric and differential scanning calorimeter analyses (TG-DSC) are performed to characterize the weight loss and transient behaviors of the raw materials. Linear thermal expansion properties are also studied. The α-cordierite phase is the only phase observed in S-3 (magnesite content 25%) sintered at 1300 °C for 2 h, and its linear thermal expansion coefficient (2.71 × 10 −6  K −1 ) is close to that of typical cordierite. Both the compressive strength (72.64 MPa) and flexural strength (23.92 MPa) of the as-synthesized samples are high with an open porosity of 33.16% and a bulk density of 1.61 g/cm 3 .